Profitability Risk and its Impact on Syrian Insurance Companies' Performance (Latakia University Journal - Economic and Legal Sciences Series, 2018)
This research deals with an analytical study of the impact of Profitability Risk on Syrian Insurance Companies' Performance. Given the importance of insurance and its role in reducing risk, in addition to its role in improving the national economy and develop it. we will try to expand in the concept of insurance and risk which Include risk definition, risk characters, types, steps, methods of risk measuring, risk and profitability risk in the Syrian insurance companies then we calculate net insurance premium and profitability index, since 2007 until 2014, with charts. Then we will see how much the profitability effect in Insurance companies’ performance. Finally, we address our findings, recommendation and references. أثر مخاطر الربحية على أداء شركات التأمين الخاصة العاملة في سورية يتناول هذا البحث دراسةً تحليلية لأثر مخاطر الربحية على أداء شركات التّأمين السورية. انطلاقاً من أهمية التأمين ودوره في الحد من المخاطر التي تتعرض لها الشركات السورية إضافة إلى دوره في تحسين الاقتصاد الوطني ودفع عجلة التنمية والتطور نحو الأمام، سنحاول في هذا البحث التوسع بمفهوم المخاطر، حيث ننطلق بدايةً بالمنهجية العلمية ثم نبدأ باستعراض لمحة عن المخاطر تتضمن تعريف الخطر، خصائصه وأركانه، تقسيماته، درجته، طرق قياس الخطر وصولاً إلى المخاطر في شركات التأمين السورية ومخاطر الربحية فيها، وبعدها نستعرض بدراسة تحليلية مؤشر الربحية لكل شركة من شركات التأمين الخاصة الداخلة في عينة البحث على مستوى السوق السورية للتأمين منذ عام 2007 حتى عام 2014، لمعرفة مقدار تأثير الأقساط في ربحيتها وقد تمت الإستعانة بالجداول اللازمة للتوضيح، وأخيراً نتطرق لأهم النتائج والتوصيات والمراجع.